Complications and Transfusions on Therapeutic Anticoagulation After Trauma. Issue 10 (October 2022) - Siletz, Anaar E.; Dhillon, Navpreet K.; Fierro, Nicole M.; Muñiz, Tobias; Loran, Priya; Singer, Matthew; Hashim, Yassar M.; Ley, Eric J.
Introduction: Trauma patients who develop indications for therapeutic anticoagulation (TAC) present a challenge due to concern for bleeding. Transfusion requirement has been described as a common complication of TAC after trauma but its clinical relevance is unclear. Objective: Determine risk factors for and clinical outcomes associated with transfusion requirement on TAC after trauma. Methods: All trauma patients admitted to an academic urban level I trauma center from January 2010 to August 2020 who received TAC were included in this retrospective cohort study. Data included injury characteristics; TAC indication and timing; transfusions; and interventions. Patients who required transfusion after TAC were compared to those who did not. Results: Eighty-two patients were included. The most common reasons for TAC were deep vein thrombosis (67.1%) and pulmonary embolism (31.7%). Two (2.4%) patients developed gastrointestinal bleeding. One (1.2%) underwent endoscopic intervention. Two patients (4.9%) had intracranial hemorrhage progression. Blood transfusion after TAC initiation was required in 43.9% of patients. Patients who were transfused started TAC more quickly after traumatic injury (5.5 vs 10.0 days, P = .03), had fewer hospital-free days (54 vs 64 days, P < .01), ICU-free days (8.5 vs 16.5 days, P = .01), and higher mortality (13.9% vs 2.1%, P = .04). Conclusion: Transfusions are common after starting TAC in trauma patients. Requiring transfusion after starting TAC was associated with shorter time from injury to starting TAC, higher mortality, and fewer ICU and hospital-free days.